Peningkatan Pemahaman Nilai-nilai Religius dan Kepercayaan Diri Ibu-ibu Lansia melalui Program Day Care - Muchtar, Nicky Estu Putu; Muflich, Moch. Faizin; Inayah, Karimatul; Aprilianto, Dwi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
This study aims to enhance the understanding of religious values and self-confidence among elderly women at Panti Werdha Mental Kasih Lamongan through a day care program. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that: 1) the implementation of the day care program through religious values involves activities that encompass elements of faith, worship, and morality, while self-confidence includes aspects of behavior, emotion, and spirituality. 2) The effectiveness of enhancing the understanding of religious values and self-confidence among elderly women through the day care program, based on interviews and field observations conducted continuously and sustainably every day, was concluded to show a 75% improvement. 3) The impact of improving the understanding of religious values includes being faithful, devout, moral, optimistic, and humble. In contrast, the character impact of self-confidence among elderly women includes being more self-assured, courageous in expressing themselves, learning new skills, and being independent. The day care program at Panti Werdha Mental Kasih Lamongan offers various activities such as public religious studies, regular elderly discussions, counseling activities, group exercises, elderly community service, creative life skills, art performances, and elderly health posts (posyandu lansia). This study contributes to providing solutions to improve the quality of life for the elderly.